A formação da vontade democrática como princípio educativo : uma análise a partir do pensamento de Jürgen Habermas - Melo, Elvis Francis Furquim de (Universidade Federal de São Carlos, 2016)
This thesis addresses the democratic will-formation as an educational principle from Habermas’s philosophy. The theoretical and exploratory path followed by Habermas shows the theoretical feasibility of the proposition that underpins the thesis. Therefore, we present the law category as intermediation between the system and the world of life. The building of opinion and will-formation is rooted in the democratic procedure of discursive law that underlies the communicative freedom process. This is explained by the mediating processes of social communications, in which free citizens, committed to the political and public will-formation, are involved. Habermas proposes the formation of a modern society from the idea of a theory of the social communication of law, as an analysis of democratic and educational practices. In Habermas’s “Communicative acting theory”, published in 1981, the category "system" is characterized by an action of the strategic-instrumental type and the category "world of life", by the symbolic, intuitive and reconstructive production, in which the law plays a crucial role in social integration. In his work “Law and democracy: between facticity and validity”, written in 1992, discursive law constitutes a possibility of intermediation between the system and the world of life, as it works as an integrating element of the democratic society. The communication of a social freedom between citizens willing to act without coercion is an alternative to a free and emancipatory formation in education. Deliberative politics is legitimate in the discursive law, which is grounded on a broad process of democratic will-formation, which is dealt here as an educational principle mandatory for democratic societies establishing.
Keywords: Democracia e direito; Mundo da vida e sistema; Jürgen Habermas; Formação da vontade democrática; Democracy and law; World of life and system; Democratic will-formation; CIENCIAS HUMANAS::EDUCACAO